Diseño de adaptaciones curriculares en la educación superior para estudiantes con discapacidad intelectual de la Universidad Nacional de Loja, periodo 2024. - Castillo Rogel, Angie Stephanie (2024)
The curricular adaptations’ development in Higher Education for students with intellectual disabilities at the Universidad Nacional de Loja, is based on the provisions of national and institutional regulations, however, through this research we could identify some obstacles that teaching staff still face when developing curricular adaptations. Since this research was executed at the Universidad Nacional de Loja during the period March-August 2024, the following objectives were set: to characterize the curricular adaptations development by the educational personnel, to identify challenges and obstacles that the teaching staff face when applying curricular adaptations, and to arise a proposal that allows them to overcome this problem. For the realization of his paper, we used a descriptive and transversal methodology with a mixed approach, given that quantitative and qualitative information was collected, integrated and analysed, applying inductive, deductive, analytical and synthetic methods, as well as techniques such as the survey aimed at teachers, and semi-structured interview to University Welfare personnel. The most relevant results encountered indicate that 47.5% of teachers have not received specific training on curricular adaptations, 38.5% sometimes collaborate with other professionals to design them, 45% consider the lack of institutional support, and 41% point to the absence of institutional guides as the main barrier; based on these results, a proposal focused on the development of a strategies manual for the design of curricular adaptations for students with intellectual disabilities was proposed, which is structured for the learning components in contact with the teacher, experimental and autonomous practice; it will also enhance the teaching and learning process of students with intellectual disabilities, and will lead to new research related to the matter of study.